DIGITAL LITERACY IN SPECIAL EDUCATION: A CASE STUDY OF TEACHING MUSIC TECHNOLOGY ONLINE TO A SPECIAL NEEDS LEARNER - Makris, Ioannis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The Covid-19 pandemic and the lockdowns enforced by many countries resulted in indispensable adjustments to the way people live and communicate. The introduction of online education in secondary and tertiary education was one such adjustment and gave rise to a new dynamic whose educational angle and potential were unknown to many teachers. Special Education teachers in particular encountered difficulties with online teaching, stemming from a number of issues common in their field: lack of uniformity special education cases present; the confusion and stress of special needs learners when faced with the teacher’s physical absence; a dearth in studies on teaching Music Technology to people with mental disabilities; and the fact that Music Technology necessitates that learners already be in possession of certain digital skills. The present study aims at presenting not only its researchers’ systematic recording of their teaching approach but also of the researchers’ actions (March 2020 lockdown-present) regarding the teaching of Music Technology online to a learner with Down syndrome, through differentiated teaching, motivation, steady interaction, and communication. Assessment was accomplished through systematic observation of the learning process, successful completion by the special needs learner of specially designed actions, and semi-structured interviews at the end of every session.